Characterization and cytoskeletal association of a major cell surface glycoprotein, GP 140, in human neutrophils. - Suchard, S J (1989)
The binding of specific ligands to neutrophil cell surface receptors and the association of these receptors with the cytoskeleton may represent an essential step in activation. To identify surface proteins that are linked to the cytoskeleton during activation, neutrophil 125I-surface labeled plasma membranes were extracted with Triton X-100, and the soluble and insoluble (cytoskeleton) fractions analyzed by SDS-PAGE and autoradiography. The major cell surface proteins recruited to the cytoskeleton after activation with Con A, FMLP, zymosan-activated serum, or immune complexes possessed a relative molecular mass in the range of 80 to 13 kD. In addition to these proteins, WGA stimulates the recruitment of a 140-kD protein (GP 140) to the cytoskeletal fraction. That GP 140 is a WGA-binding protein was verified by Western blotting and WGA-Sepharose affinity chromatography. The Coomassie blue staining pattern of the WGA cytoskeletal fraction revealed major protein bands at apparent molecular weights of greater than 200 (approximately 250, 240, 235), 200, 115, 82/78 (a doublet), 56, 43, 36, and 18 kD. Labeling cells with 32PO4 before WGA treatment indicated that the cytoskeletal proteins with molecular weights of 115, 82/78, and 72 kD, and a 40-kD detergent soluble protein, are phosphorylated during activation. The 78 kD cytoskeletal phosphoprotein co-migrates with the lower subunit of erythrocyte (RBC) band 4.1 and shows strong cross-reactivity with RBC anti-band 4.1 antibody. Phosphorylation of cytoskeletal proteins like 4.1 may be involved in the regulation of interactions between GP 140 and the actin-containing cytoskeleton. Unlike the C3bi receptor, GP 140 is a major surface component of unactivated PMNs, has no stoichiometrically related 95-kD subunit, and has two isoforms with pIs in the range of 6.4 to 6.6. Under conditions that result in an increased expression of the C3bi receptor (such as treatment with the Ca2+ ionophore A23187), the amount of GP 140 on the PMN cell surface appears to be significantly reduced. The interaction of GP 140 with the cytoskeleton during activation suggests that GP 140 may play an important role in neutrophil functional responses.